A study of the variation in some structural features and some wood properties of Pinus caribaea - Ong, S (1978)
﻿ Wood density and fibre morphology of Pinus caribaea var. hondurensis Barrett and Golfari from Fiji were studied in relation to pulp properties. Densitometry and anatomical measurement were examined using billets taken from a sub-sample of 20 12-13 year old trees, chosen as representative of the density range observed in a first sample of 120 trees. Pulping properties were examined at the Tropical Products Institute, London. Considerable differences between trees were found in all characteristics examined and all characteristics showed fairly marked tree to tree variation in development patterns in a radial direction though differences along the stem were small. Between ring differences for ring width, density, cell wall thickness and cell wall percentage were considerable but cell lumen width and cell diameter were fairly constant between rings. Tree morphological characteristics cannot be used for estimation of whole tree values for any of the features studied. Whole tree values for wood characteristics can be accurately predicted from samples taken at 5% height level. Characteristic patterns of wood density distribution classes and tracheid cross sectional dimension classes were found, resembling chi-squared, binomial and bimodal curves. Wood properties could be used to predict pulp yield percentage and tear factor accurately by simple regression, less precise estimates could be obtained in this way, for burst factor and breaking length, which were best indicated by cell wall thickness. The best indicators of variation in pulp total yield percentage were chemical properties. Density was the best indicator of tear factor whilst cell wall thickness was the most important factor in explaining burst factor and breaking length. Growth rate showed negative correlation with wood density; trees of lower density produce paper of a strength generally at least equal to that obtained with higher density trees, though tear factor was lower. Thus the selection of trees for fast growth rate is suggested as the most profitable course. The most desirable selection criteria are listed.